Occular Drug Delivery System: A Novel Review with Applications - Prasanthi Samathoti (Asian Journal of Pharmaceutics (AJP), 2025)
Among the many drug delivery systems, ocular drug delivery system,maintaining a therapeutic drug level at the site of action, is one of the most difficult issues pharmaceutical researchers and associates face for a long time. Programmable medication delivery mechanisms provide a lot benefits, positive aspects in standard amount methods within regards for reduce dosing frequency, nontoxic and biocompatible, either water-friendly as well as a lipophilic substances had been enclosed, targeted drug delivery can be achieved, improves dissolution, therefore improving an accessibility of substances, large scale production is possible, intended medication delivery in simple exterior alterations, stops deterioration of a lipophilic substances and provides over time equilibrium, prevents medication explosion upon storage, prepared employing a combine of a solid and a liquid lipids as an essential matrices, clear, thermodynamically secure formulations with a droplet size of 100 nm, prevents general distribution, enhances beneficial effectiveness, protects drug form deterioration, elevates intercellular penetration, thus enhancing absorption by using niosomes, discomes, cubosomes, nanowafers, dendrimers, polymer-drug conjugates, nanosuspensins, nanoemulsions, polymeric nanomiccelles, surfactant nanomicelles, polyion complex nanomicelles, nanostructure lipid carriers, solid lipid carriers, liposomes, polymeric nanoparticles, viscosity enhancers, produrg, ocular iontophoresis, hydrogels, nanoparticles, contact lens, microneedles, in situ gelling system, microemulsion, sonophoresis, phototherapy, and various medications through implants. These numerous designs have been made for some of the special routes of drug delivery such as Intravitreal administration, intracameral, perilocular, suprachoroidal, subconjunctiva, topical, and systemic with various mechanisms. The marketed preparations, such as natamycin solid lip nanoparticles, ciprocin, dex in isotonic acetate buffer, ophthalmic emulsion, napafenacc ophthalmic suspension, etc., are available in various modes of drug delivery.